A redefinition of the Curculionini of the world, with a key to subtribes and genera, and two new genera: Pseudoculio and Megaoculis (Coleoptera: Curculionidae: Curculioninae) - Pelsue, Jr., Frank W.; O’brien, Charles W. (Zootaxa, 2011)
A key to the subtribes and genera of the Curculionini is presented, and two new genera are described: Pseudoculio with Curculio (Balaninus) discreticoxis Marshall, as its type species (new combination); and Megaoculis with Megaoculis egeri, new species, as its type species. Keys to the species of the new genera are provided. Photos of habitus are included for most taxa and of genitalia of the new species. The following taxa are described as new in this paper: subtribes Archariina, new subtribe, Erganiina, new subtribe, and Labaninina, new subtribe; and new species: Pseudoculio barclayi, new species, P. confusicoxis , new species, P. crinitus, new species, P. promissus, new species, P. spiesi, new species, and P. vittatus, new species. Curculio guyanensis Rheinheimer is reassigned to the new genus Megaoculis, new combination. The following genera placed in Incertae sedis in Alonso-Zarazaga and Lyal are removed from the tribe: Allocionus Hustache, Balaninorhynchus Fairmaire, Bradyninus Fairmaire, Semicardius Hustache and Trichanthonomus Hustache.